Evaluation of various mathematical models in describing ruminal degradability of protein sources - Bediye, S.; Umunna, N.N.; Nsahlai, I.V.; Sileshi, Z.; Yami, A. (Ethiopian Society of Animal Production, 1998)
Five mathematical models were evaluated for their ability to describe ruminal degradability profiles of protein sources composed of herbaceous legumes, browse species and oilseed cakes. Degradability constants of dry matter, organic matter, nitrogen and neutral detergent fiber of the feeds were taken into account. Tests of regression coefficients, analysis of residual behavior and ocnsistencies in parameter estimates were adopted for model comparison and validation. The conventional exponential model was the best for all feed classes in describing DM, OM and N disappearance while the exponential decay model was the best in describing degradation profile of NDF for all feed classes.